Modification of kosaric’s medium with nitrogen and phosphorus for Spirulina (Arthrospira platensis) in sheltered open culture system - Mashor, Nurshazreen (2015)
Presently the world is experiencing serious environmental crisis such as global warming that effect the source of human nutrition hence, increasing starvation, and malnutrition. Demand for microalgae as supplemental food had increased steadily in recent years. However, in Malaysia, cultivation of microalgae is scanty due to lack of knowledge in microalgae production in variable weather conditions. One of the fundamental problems is lack of cheap and effective fertilizer. The aim of this research was to develop economical and inexpensive fertilizer for a commercial production and give higher productivity of A. platensis. The objective was implemented by substituting all the nitrogen and phosphorus sources present in Kosaric Medium (SM) with locally available commercial fertilizers. The A. platensis was treated with 19 treatments include SM as control with three different nitrogen sources (ammonium nitrate, ammonium sulphate, and urea) and three different phosphorus sources (phosphoric acids, triple superphosphate (TSP), and diammonium phosphate (DAP)). Two grades of nitrogen concentration representing 50% (high concentration) and 25% (low concentration) of SM nitrogen concentration were compared in this study. 30L A. platensis was grown in each polyethylene (PE) bag in outdoor condition for seven days in first cultivation, ten days in second cultivation and 8 days in third cultivation. The growth parameters (optical density, biomass and chlorophyll a concentration) and biochemical content (proteins, carbohydrate and lipid) were recorded and compared with A. platensis cultivated in SM. Significant differences of the growth parameters and biochemical composition were recorded for the different nitrogen and phosphorus sources and concentration. The result of this study revealed that A. platensis cultivation during dry season had better performance and A. platensis could utilize ammonium nitrate (ammonium nitrate + triple superphosphate in low concentration) most efficiently and gave the highest productivity on day 8 with biomass, chlorophyll, and protein yield of 1.24 ± 0.004g/L, 11.41 ± 0.21mg/l, and 62.5%, respectively with average of pH, 10.12 ± 0.08 which was significantly different (p<0.05) with other treatments. This was better than that of SM (0.73± 0.01g/L, 8.64 ± 0.13mg/L, and 52%, respectively). Further increased in nitrogen concentration will limit growth. This study indicated that the utilization of ammonium nitrate and TSP as nitrogen and phosphorus has the potential to replace the expensive Kosaric media. The modified medium can be used cost effectively for large scale mass production of protein rich A. platensis and yields similar performances to Kosaric medium.